Flight 000 Refocusing the Aircraft Industry Through an End-of-Life Aircraft Recycling Facility - Lontok, Norman Dominic V. (College of Architecture, University of the Philippines Diliman, 2020)
Pasay City, with the steady increase in the number of passengers and flights, also faces retirement of aircrafts which hit its maximum operation hours. When an aircraft loses its airworthiness, its value is analyzed as to which between recycling and disposal is a better option. This study aims to show the benefits and opportunities present in aircraft recycling and serve as a model for future developments such as this in other locations in the Philippines. This project viewed aircraft recycling as a practice rooted with the principles of the Circular Economy Model and the integration of Constructivist Learning Theory and Social Cognitive Theory in order to fulfill its objectives. Offline and online resources and personal interviews served as the basis in grasping the practice of aircraft recycling which resulted in an analysis of the possible users and the construction of an appropriate space programming. This study revealed that there is an opportunity for it to reach out to the community through integration of interactive spaces that is accessible to the public.